2017
DOI: 10.1007/s12350-016-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an endothelin receptor antagonist, Macitentan, on right ventricular substrate utilization and function in a Sugen 5416/hypoxia rat model of severe pulmonary arterial hypertension

Abstract: PAH is associated with metabolic changes in the RV, characterized by a marked increase in FDG and FTHA uptake. Macitentan treatment reduced PAH severity and was associated with a decrease in RV FDG uptake and improved RV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“… 9 Interestingly, macitentan was recently associated with metabolic changes in the RV of Sugen-induced PAH. 57 Consistent with this hypothesis, dual ET A /ET B receptor blockade also impacted on capillary density and perfusion within the RV and skeletal muscles in our PH model. However, part of the increases in perfusion (i.e.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 9 Interestingly, macitentan was recently associated with metabolic changes in the RV of Sugen-induced PAH. 57 Consistent with this hypothesis, dual ET A /ET B receptor blockade also impacted on capillary density and perfusion within the RV and skeletal muscles in our PH model. However, part of the increases in perfusion (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Given the tight coupling between angiogenesis and metabolism, 13 the metabolic dysregulation observed within the distal PA, RV, 9 and skeletal muscles 10 in PAH has been hypothesized to contribute to this capillary rarefaction in PAH 9 . Interestingly, macitentan was recently associated with metabolic changes in the RV of Sugen‐induced PAH 57 . Consistent with this hypothesis, dual ET A /ET B receptor blockade also impacted on capillary density and perfusion within the RV and skeletal muscles in our PH model.…”
Section: Discussionsupporting
confidence: 84%
“…PET studies have shown substantial increases in 18 FDG uptake in the RV of both animals and humans with RV hypertrophy [ 90 ] and PAH [ 79 , 90 92 ] ( figure 3a ). More recent studies have determined that such increased RV 18 FDG accumulation portends a poorer prognosis [ 97 ], while treatment with agents such as macitentan can attenuate such uptake concomitant with an improvement in RV function and haemodynamics [ 98 ]. PET is useful for investigations into drug distribution, target binding and drug-induced biochemical responses; however, its cost and limited availability currently restricts its use.…”
Section: Diagnostic Application Of Metabolic Dysregulation In Phmentioning
confidence: 99%
“…Future perspectives beyond simple improvement in hemodynamics will focus on utilization of right-ventricle substrates and the effects of ERAs on right-ventricle remodeling and biventricular fibrosis. 76 , 77 In the near future, assessment of ERA efficacy on right-ventricle remodeling will rely increasingly on cardiac magnetic resonance imaging. Moreover, new ERAs will be tested (eg, HJP272), and other ERAs will be tested in diseases other than PAH (eg, chronic kidney disease, mainly for diabetic nephropathy).…”
Section: Future Developmentsmentioning
confidence: 99%